2020
DOI: 10.1111/jonm.13076
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and spirituality: A discussion paper on intertwining metaparadigms

Abstract: Aim To explore connections between spiritual metaparadigm and the nursing metaparadigm and advocate for a progressive spiritualization of nursing management. Background Relationship between the spiritual holistic metaparadigm of love, communion and gift and the holonic nursing metaparadigm of care, relationship and practice is not completely understood. Method The construction of a theoretical explanation on the basis of accumulated knowledge in the fields of nursing and spirituality (especially Christian spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The four variables grouped by the third factor would seem to confirm the idea already found in the literature that spirituality is not a concept associated only with religion but also a universal concept, able to unify people, therefore also atheists and agnostics (Domingo-Osle & Domingo, 2020;McSherry et al, 2002;Mcsherry & Jamieson, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…The four variables grouped by the third factor would seem to confirm the idea already found in the literature that spirituality is not a concept associated only with religion but also a universal concept, able to unify people, therefore also atheists and agnostics (Domingo-Osle & Domingo, 2020;McSherry et al, 2002;Mcsherry & Jamieson, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Bringing spiritual care into practice is challenging, but it is a critical dimension for some individuals with mental health problems and families and should be considered in nursing practice, thorough models of care that could be implemented, tested and improved at a point to keep cultural and religious sensitivity. Specifically, regarding nursing science, nursing theorists have raised the importance of spirituality in different theories and models of care (Domingo‐Osle & Domingo, 2020). It is suggested that nursing can be a sacred art when nurses move beyond the satisfaction of needs and touch the person as a whole (Watson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This universal character of nursing solidarity demands a multidimensional or holistic approach to nursing solidarity, which implies the recognition of the physical, emotional, psychological, social, and spiritual dimensions of each person and their families and communities. 37,41–44 This holistic approach is not optional but is the only approach compatible with practicing profound solidarity in nursing and therefore the only one possible according to the definition of solidarity this article proposes.c) Plurality of persons : Nursing solidarity requires a relation of holistic interdependence between at least two persons: a patient and a nurse. They develop a true partnership in which each one has a specific role.…”
Section: Defining Nursing Solidaritymentioning
confidence: 99%